THE ROLE OF INSPIRATIONAL LEADERSHIP IN ENHANCING ORGANIZATIONAL COMMITMENT AMONG WORKING INDIVIDUALS AT TIKRIT UNIVERSITY: AN APPLIED STUDY - Firas Hassan Rashid; Mohammed Mahmood Abdullah; Mezhir Abdullah Ahmed (Scholar Express Journals, 2022)
The research dealt with the study of the role of inspirational leadership in enhancing organizational commitment among individuals working at Tikrit University. Through a random sample of individuals working at the university in question, which numbered (72) individuals distributed over the different faculties of the university. Where the research reached a set of conclusions, the most important of which is the validity of the research hypotheses, as well as the existence of a significant statistically significant effect of the inspiring leadership by removing it (self-confidence, future vision, and recognition of the leader as a tool for change ).
Keywords: inspirational leadership; self-confidence; future vision